An NMR Study of the Bortezomib Degradation under Clinical Use Conditions - Adele Bolognese; Anna Esposito; Michele Manfra; Lucio Catalano; Fara Petruzziello; Maria Carmen Martorelli; Raffaella Pagliuca; Vittoria Mazzarelli; Maria Ottiero; Melania Scalfaro; Bruno Rotoli (Advances in Hematology)
The (R)-3-methyl-1-((S)-3-phenyl-2-(pyrazine-2-carboxamido)propanamido)butyl-boronic acid, bortezomib (BTZ), which binds the 20S proteasome subunit and causes a large inhibition of its activity, is a peptidomimetic boronic drug mainly used for the treatment of multiple myeloma. Commercial BTZ, stabilized as mannitol derivative, has been investigated under the common conditions of the clinical use because it is suspected to be easily degradable in the region of its boronic moiety. Commercial BTZ samples, reconstituted according to the reported commercial instructions and stored at 4∘C, were analyzed by high-field nuclear magnetic resonance spectroscopy in comparison with identical samples bubbled with air and argon, respectively. All the samples remained unchanged for a week. After a month, the air filled samples showed the presence of two main degradation products (6% of starting material), the N-(1-(1-hydroxy-3-methylbutylamino)-1-oxo-3-phenylpropan-2-yl) pyrazine-2-carboxamide (BTZ1; 5%, determined from NMR integration) and the (S)-N-(1-(3-methylbutanamido)-1-oxo-3-phenylpropan-2-yl)pyrazine-2-carboxamide (BTZ2; 1%, determined from NMR integration), identified on the basis of their chemical and spectroscopic properties. The BTZ1 and BTZ2 finding suggests that, under the common condition of use and at 4∘C, commercial BTZ-mannitol is stable for a week, and that, in time, it undergoes slow oxidative deboronation which partially inactivates the product. Low temperature and scarce contact with air decrease the degradation process.